Public Service Motivation: A Conflict Triangle of Compassion, Self-sacrifice and Work–Family Life Balance. (March 2017) - Azhar, Aisha
This case discusses the situation of a novice scholar, Dr Maryam Ali, who has to decide between accepting an attractive job offer in a different city or staying in her current position to work on a community project aimed at empowering poor women in a small town in Khyber Pakhtunkhwa (KPK). The case explains how Maryam, while writing a grant proposal, gets to know the harsh financial realities of the extremely poor women of the local area. While she wins the grant for the project, she is offered an attractive job in another city. Given her family circumstances, particularly her husband's job and the kids' schooling, Maryam should immediately move to the other city. However, Maryam does not want to move without completing the project that gave much hope to the needy women for initiating small-scale earnings. The intrinsic motivation to actually help the poor women eventually superseded her desire for extrinsic rewards to earn professional recognition for executing the community project. Her decision to run the project led to tensions and arguments between the couple. The case examines interesting ways to explore and debate compassionate orientation of a highly career-oriented woman. The case exposes the participants to a variety of issues related to public service motivation including self-sacrifice, compassion, commitment to public interest and work–family life balance.